The dedicated nurse in the multiple sclerosis centre: effects on the self-management capacity in home therapy patients - Elena Mutta; Eugenia Tomas Roldan; Martina Boccardo; Marika Radici; Mariagrazia Esposito; Silvia Fermi; Sebastiano Giuseppe Crisafulli; Stefania Cappiello; Patrizia Carta; Marcello Vargiu; Elisabetta Casella; Caterina Barrila; et al. (Dissertation Nursing)
Introduction People affected by multiple sclerosis require a continuous system of care. The optimum position to coordinate care can be obtained with nurse, within an MS Centre, who provide a range of abilities for patients oriented toward self-management of the pathology.